Just Medicare : What's In, What's Out, How We Decide. - Flood, Colleen M. (University of Toronto Press, 2006)
Just Medicare illustrates that legal scholars can also contribute to the issue of how to allocate scarce health resources by determining what constitutes fair processes for decision-making, and by challenging unjust processes.